$$
\begin{align}
\sum_{n=1}^\infty(-1)^{n-1}\frac1n\sum_{k=1}^n\frac1{k^2}
&=\sum_{k=1}^\infty\sum_{n=k}^\infty(-1)^{n-1}\frac1{nk^2}\\
&=\sum_{k=1}^\infty\sum_{n=k+1}^\infty(-1)^{n-1}\frac1{nk^2}+\sum_{n=1}^\infty(-1)^{n-1}\frac1{n^3}\\
&=\sum_{k=1}^\infty\sum_{n=1}^\infty(-1)^{n+k-1}\frac1{(n+k)k^2}+\frac34\zeta(3)\\
&=\sum_{k=1}^\infty\sum_{n=1}^\infty(-1)^{n+k-1}\left(\frac1{k^2n}-\frac1{(n+k)^2}\left(\frac1k+\frac1n\right)\right)+\frac34\zeta(3)\\
&=-2\sum_{k=1}^\infty\sum_{n=1}^\infty(-1)^{n+k-1}\frac1{k(n+k)^2}-\frac12\zeta(2)\log(2)+\frac34\zeta(3)\\